Management Of Media Organizations (Radio And Tv) With Special Emphasis On Knowledge Management - Shirazi, Zahra Dastgheyb (The Turkish Online Journal of Design Art and Communication, 2016)
It seems that the most appropriate method to prevent deterioration and continue surviving is to increase information and dissemination of knowledge between employees of different levels of organization. Because knowledge is one of the most important and most valuable asset of any organization. The aim of this study is to examine the management of media organizations (radio and TV) with special emphasis on knowledge management. The research method was a descriptive correlational and the study population included all employees of media organizations (radio, television, press, etc.) in Tehran city and 150 employees and managers were selected and analyzed by using available sampling method. The data collection tool is a questionnaire in this study. The data obtained were analyzed through questionnaires using SPSS software and Pearson and regression statistical tests. In general, the results showed that the use of knowledge management, knowledge preservation, knowledge transfer, knowledge creation, knowledge application has positive and significant impact on the management of media organizations.
Keywords: media; radio; television; knowledge management